Nanoporous-crystalline and amorphous films of PPO including off-on vapochromic fluorescent 7-hydroxy coumarin guests. (17th May 2022) - Rizzo, Paola; Gallo, Chiara; Cozzolino, Antonietta; Coscia, Nicola; Micheletti, Cosimo; Ventura, Francesco; Minei, Pierpaolo; Pucci, Andrea
Abstract: This study examines the preparation of nanoporous-crystalline and amorphous films of poly(2, 6-dimethyl-1, 4-phenylene)oxide (PPO) containing 7-hydroxy coumarin (i.e., umbelliferone) for the detection of chloroform vapours. Chloroform is selected as the volatile contaminant model being considered harmful and possibly carcinogenic after prolonged exposure. Umbelliferone is chosen as a fluorescent molecule being mostly unemissive in the solid-state and apolar media. α and β nanoporous-crystalline and amorphous PPO films presenting ≈40 μm thickness have been prepared by casting from carbon tetrachloride, benzene and chloroform solutions, respectively, whereas umbelliferone inclusions (1–2 wt%) have been realized in saturated methanol mixtures. Films show fluorescence maximum at about 430 nm with very low quantum yield (ΦF ) of around 1–2%, and particularly reduced in the α and β PPO films, thus suggesting stronger molecular interactions which might facilitate fluorescence self-quenching. It has demonstrated that the exposure to chloroform vapours under saturated conditions (10 5 ppm) turns rapidly on the fluorescence of the polymer films thanks to the solvation effect of the solvent and in agreement with the ΦF of 7% of umbelliferone in chloroform. Notably, a slower response was detected by using dichlorometane as VOC, possibly due to the weaker H-donor strength with respect to chloroform. It was worth noting, that the phenomenon results fastest for the α PPO films, i.e., in case of the lowest ΦF and quenched emission. Vapochromism appears therefore sensitive to the different fluorophore confinement, and the reported results may open new avenues for the rapid detection of VOC vapours. Graphical abstract: Image 1 Highlights: Nanoporous-crystalline PPO films were prepared and characterized by WAXD and FTIR. Umbelliferone inclusions in PPO films showed very low ΦF of around 1–2%. Exposure to CHCl3 vapours turned the fluorescence on. Faster vapochromism for the α and β co-crystalline PPO films.